Victorian Alpine Plot Network (Alpine Summit Plots): Plot Details - Spatial Coordinates for Lowland-to-highland Roadside Transects 4WD Track Data, South-East Highlands, Australia - John Morgan (TERN Australia, 2015)
This Victorian Alpine Plot Network Road Transects 4WD Track Data Package comprises spatial data for Lowland-to-highland 4WD Roadside Transects in the South-East Highlands, Australia. Plots are located at attitudinally stratified intervals along transects. The transects follow major roads and management tracks in the Victorian Alps. Each track is divided into multiple altitudinal sectors in which generally a single plot is situated. The Alpine Summit plots study, which commenced in 2001, forms part of the collection of data packages by the Victorian Alpine Plot Network. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine.